Diversity in brokerage: how do gateway cities interlink their hinterlands?. Issue 2 (1st February 2023) - Scholvin, Sören; Breul, Moritz; Diez, Javier Revilla
ABSTRACT: The article invites readers to rethink cities in economic networks against the backdrop of the many ways in which 'gateway cities', serving as brokers, interlink their respective hinterlands globally. It adds logistics, industrial processing and knowledge transmission to the more established gateway dimensions of corporate control and related service provision. This open heuristic is applied to Buenos Aires (Argentina), Cape Town (South Africa) and Singapore, which are vital nodes for the oil and gas industry. In addition to showing how diverse brokerage by cities is, the article calls for qualitative research to complement the insights on city networks generated by quantitative assessments.